2019
DOI: 10.1002/pcr2.10057
|View full text |Cite
|
Sign up to set email alerts
|

Promoted stereocomplex formation and two‐step crystallization kinetics of poly( l ‐lactic acid)/poly( d ‐lactic acid) blends induced by nucleator

Abstract: Stereocomplex (SC) crystallization is an effective method to improve the physical performance of poly(lactic acid) (PLA) materials. However, SCs crystallization is usually suppressed by homocrystallization (HCs) of high‐molecular‐weight (HMW) poly(L‐lactic acid)/poly(D‐lactic acid) (PLLA/PDLA) blend; this restricts the preparation and processing of SC‐PLA materials. Here, a series of SC‐type nucleators is selected to add into PLLA/PDLA blends, that is, p‐xylene bisalkyl urea (XBU) compound. This type of nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…On the basis of elaborate exploration, many strategies have been reported to promote the formation of SC. These include the synthesis of stereo-block PLLA- b -PDLA, melt blending at a temperature between the melting points of SC and HC, , adding nucleating agents, , flow-induced crystallization, ,, high temperature annealing, , etc. In spite of all this effort, crystallization of pure SC still remains an unsolved challenge, especially in a high-molecular-weight (HMW) PLLA/PDLA racemate. …”
Section: Introductionmentioning
confidence: 99%
“…On the basis of elaborate exploration, many strategies have been reported to promote the formation of SC. These include the synthesis of stereo-block PLLA- b -PDLA, melt blending at a temperature between the melting points of SC and HC, , adding nucleating agents, , flow-induced crystallization, ,, high temperature annealing, , etc. In spite of all this effort, crystallization of pure SC still remains an unsolved challenge, especially in a high-molecular-weight (HMW) PLLA/PDLA racemate. …”
Section: Introductionmentioning
confidence: 99%
“…However, this method is limited because not all polymers experience as drastic of a difference in T m between its homocrystallite and stereocomplex forms. A way to address this is the addition of organic or inorganic compounds called nucleators that selectively induce stereocomplex crystallization. By specifically enhancing the noncovalent forces that drive stereocomplexation, these nucleating agents can also significantly enhance the crystallization rate of the complex. Future research needs to be done to see whether these or other methods used to enhance the crystallinity and crystallization rate of SC-PLA can be applied to other SC-polyesters or even other SC-scaffolds.…”
Section: Future Directionsmentioning
confidence: 99%
“…In comparison with liner PLLA/PDLA blends, star-shaped and comblike ones have been proven to exhibit markedly enhanced SC crystallizability, probably owing to the favored interactions between enantiomeric PLA branches and the increased segment mobility [34,[37][38][39][40][41]. Nevertheless, such unique PLAs have not been industrially produced up to now, so considerable efforts have recently been devoted to gain exclusive SC crystallization of commercial linear high-MW PLLA/PDLA blends by incorporating certain processing additives (e.g., plasticizers [42][43][44], compatibilizers [22,45,46], and nucleating agents [47][48][49][50]). For example, Yang et al [51] first reported that poly (ethylene glycol) (PEG) can facilitate the SC crystallization of PLLA/PDLA blends by increasing segment mobility and diffusion ability as a plasticizer.…”
Section: Introductionmentioning
confidence: 99%